PHILOSOPHY OF EDUCATION FOR INDONESIA, PRESENT AND FUTURE - Corina Rahayu; Hadijah Bunga Maharani (Proceeding International Seminar of Islamic Studies, 2022)
Children's mental health is how children think and feel about themselves and the world around them. Therefore, mental health is related to how children deal with challenges.children's mental health can be affected by many things, including family circumstances, school life, and life events. Therefore children can experience mental health problems.Parents often underestimate the mental health of their children, including in the Bandar Khalipah village area.The purpose of this study is for parents to pay more attention to the mental health of their children.The subjects of this study were several children whose mental health had been neglected by their parents.The method used is a qualitative method in the form of a case study.Keywords: influence' the parents'child mental health'